23 The association of cognitive impairment and coronary artery disease burden in older patients with non-st elevation acute coronary syndrome. (27th November 2017) - Gu, Sophie Zhaotao; Batty, Jonathan; Jordan, Rebecca; Veerasamy, Murugapathy; Sinclair, Hannah; Bagnall, Alan; Purcell, Ian; Spyridopoulos, Ioakim; Egred, Mohaned; Zaman, Azfar; Das, Rajiv; Edwards, Richard; et al.
Abstract : Introduction: The relationship between cognition and complexity of coronary artery disease (CAD) measured by Syntax score and British Cardiovascular Intervention Society Jeopardy Score (BCIS JS) in older patients presenting with non ST elevation ACS (NSTEACS) is not known. Method: 277 patients ≥75 years of age, admitted for invasive management of NSTEACS, were enrolled into a 2-centre prospective observational study-ICON1 study (NCT01933581 ). Cognitive assessment was performed by Montreal Cognitive Assessment (MoCA) test (Impaired- MoCA <26 [CI]; Not impaired- MoCA ≥26 [NI]). Syntax 1.0 risk calculator and BCIS algorithm were used to calculate Syntax and BCIS JS. Procedure complication includes dissection, distal embolization, abrupt closure, thrombus, perforation and loss of side branch evaluated at Newcastle Angiographic core lab. Results: 251 patients had MoCA test at presentation (mean ±SD=25.1±3.3) Table 1. CI group had more left main (LM) or triple vessel disease (3VD) compared to NI group (39.2% vs 24%, p=0.01). No difference was found in proportion of SYNTAX score >22 (32.2% vs 23.1%, p=0.12), proportion of BCIS jeopardy score ≥6 (63.6% vs 60.9%, p=0.661) and presence of moderate or severe calcification (51.2% vs 40.5%, p=0.09) between CI and NI groups. Overall procedure complication rate is low at 4.5%, with no difference in complication rate between the 2 groups (3.2% vs 5.7%, p=0.504). Conclusion: In this selected high-risk older patient cohort, cognitive impairment is associated with higher proportion of LM or 3VD. CAD complexity and coronary calcification are not significantly different.